Thiazolidinedione and cardiovascular risk in type 2 diabetes mellitus - Yenny, Yenny (Faculty of Medicine, Trisakti University, 2008)
Cardiovascular disorders are the most common complications encountered in patients with type 2 diabetes mellitus (DM). The relationship is likely to be multifactorial and may also involve a specific, though ill-defined, diabetic cardiomyopathy. Patients with heart failure accompanied by DM have a reduced cardiac output compared with patients without DM. Thiazolidinediones (TZDs) are agonists of peroxisome proliferator-activated receptor gamma (PPARÃ£) and have beneficial effects in the control of blood glucose and cardiovascular parameters, but the ability of these drugs to induce retention of plasma has to be taken into consideration in prescribing them for patients with DM at high risk of cardiovascular disease. The molecular mechanism of fluid retention by TZDs has not been fully elucidated. Available evidence indicate a possible role of epithelial sodium channels (ENaC) in causing the side effects of TZDs. This paper will discuss the mechanism of ENaC in inducing fluid retention and the management to be applied for anticipating these side effects.